Age, diabetes mellitus, and dialysis modality are associated with risk of poor muscle strength and physical function in hemodialysis and peritoneal dialysis patients - Silva, Maryanne Zilli Canedo [UNESP]; Antonio, Karina Jesus [UNESP]; Reis, João Marcos Soares; Alves, Leticia Salmazzo; Caramori, Jacqueline Costa Teixeira [UNESP]; Vogt, Barbara Perez (My University, 2021)
Background: Due to the poor outcomes associated with the impairment of physical function and muscle strength in patients on maintenance dialysis, it is important to understand the factors that may influence physical function and muscle strength. The aim of this study was to explore the factors associated with physical function in hemodialysis and peritoneal dialysis patients. Methods: Patients with chronic kidney disease on dialysis for at least 3 months, aged 18 years old or above, were enrolled. Physical function was assessed by handgrip strength, gait and sit-to-stand tests, and the Short Physical Performance Battery (SPPB). Clinical and laboratory data were collected to verify the association with physical function parameters through binary logistic regression. Results: One-hundred ninety patients on maintenance dialysis were included; 140 patients (73.7%) on hemodialysis and 50 (26.3%) on peritoneal dialysis. The mean age was 57.3 ± 14.9 years, 109 (57.4%) were male, and 87 (45.8%) were older than 60 years. The median SPPB was 8.0 points (6.0-10.0 points) and the mean ± standard deviation of handgrip strength was 24.7 ± 12.2 kg. Binary logistic regression showed that age, type of renal replacement therapy, diabetes mellitus, and serum creatinine were significantly associated with both higher 4-meter gait test times and lower SPPB scores. Only age and diabetes mellitus were associated with higher sit-to-stand test times, while age and ferritin were associated with lower handgrip strength. Conclusion: Age, diabetes mellitus, serum creatinine, and hemodialysis modality are factors related to physical function in dialysis patients.
Keywords: Chronic renal insufficiency; Dialysis; Hand strength; Physical functional performance; Physical performance